Effect of a Change Management Program in a Medical Device Reprocessing Department: A Mixed Methods Study. Issue 1 (April 2014) - Chadwick, Judy; Knapp, Mike; Sinclair, Douglas; Arshoff, Larry
Faced with a variety of challenges in relation to performance, quality, staff engagement and morale in the Medical Device Reprocessing Department, managers at St. Michael's Hospital developed and implemented several innovative approaches including combining staff training and performance metrics. The results of these initiatives included a substantial reduction in the departmental budget along with higher productivity, output and quality; better staff morale; an improved relationship between management and the union; and a stronger partnership between the department and its institutional customers.